3D printed tissue engineered model for bone invasion of oral cancer. (June 2018) - Almela, Thafar; Al-Sahaf, Sarmad; Brook, Ian M.; Khoshroo, Kimia; Rasoulianboroujeni, Morteza; Fahimipour, Farahnaz; Tahriri, Mohammadreza; Dashtimoghadam, Erfan; Bolt, Robert; Tayebi, Lobat; Moharamzadeh, Keyvan
Highlights: Normal human alveolar bone-mucosal relationship can be engineered in vitro. The characteristics of the composite model were closely comparable to normal tissue counterpart. The development of 3D multi-layered oral cancer model provides a representative tool for oral cancer studies. Abstract: Recent advances in three-dimensional printing technology have led to a rapid expansion of its applications in tissue engineering. The present study was designed to develop and characterize an in vitro multi-layered human alveolar bone, based on a 3D printed scaffold, combined with tissue engineered oral mucosal model. The objective was to incorporate oral squamous cell carcinoma (OSCC) cell line spheroids to the 3D model at different anatomical levels to represent different stages of oral cancer. Histological evaluation of the 3D tissue model revealed a tri-layered structure consisting of distinct epithelial, connective tissue, and bone layers; replicating normal oral tissue architecture. The mucosal part showed a well-differentiated stratified oral squamous epithelium similar to that of the native tissue counterpart, as demonstrated by immunohistochemistry for cytokeratin 13 and 14. Histological assessment of the cancerous models demonstrated OSCC spheroids at three depths including supra-epithelial level, sub-epithelial level, and deep in the connective tissue-bone interface. The 3D tissue engineered composite model closely simulated the native oral hard and soft tissues and has the potential to be used as a valuable in vitro model for the investigation of bone invasion of oral cancer and for the evaluation of novel diagnostic or therapeutic approaches to manage OSCC in the future.